The experimental prophylaxis of the peroxide periodontitis by antidysbiotic means - Levitsky, A. P.; Makarenko, O. A.; Selivanskaуa, I. A.; Sevostianova, T. A.; Furdychko, A. I.; Tomilina, T. V.; Stupak, E. P.; Markiv, A. V. (Journal of Education, Health and Sport, 2017)
Aim: To determine the periodontoprotective properties of antidysbiotic means (ADM) at the peroxide periodontitis. Methods: ADM (quertulyn, lequin, lecasil and lysozyme-forte) were used. The peroxide periodontitis was reproduced by peroxide sunflower oil introduction in during 2,5 month. The levels of MDA, elastase, urease, lysozyme, catalase were determined into gum. The levels of alkaline and acid phosphatase, calcium and protein were determined into periodontal bone. Results: The introduction of ADM the reduced the levels of inflammation markers (MDA and elastase) and to the degree of dysbiosis but raised the levels of lysozyme and catalase into gum. ADM reduced the acid phosphatase activity but raised the alkaline phosphatase into bone. Conclusion: Lequin was more effective means as antiinflammation, quertulyn was more effective means as antidysbiotic action, lysozyme-forte was more effective means mineralization action. The lecitine contents means lequin and lecasil possessed more effective action on the degree mineralization of periodontal bone.